2009
DOI: 10.1007/978-3-642-03885-3_148
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of body fluid in patients with chronic heart failure using Bioimpedance - Spectroscopy

Abstract: Patients with chronic heart failure (CHF) often suffer from the formation of edema within their body. To monitor the appearance of such edema in lung and limbs as early as possible would improve the medical treatment fundamentally. Bioimpedance-Spectroscopy is a non-invasive, easyto-implement measurement method that allows determining the water content of a patient. However, stable long term measurements are difficult to perform and so the optimal measurement conditions have to be defined precisely. In the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…These end-spectrum frequencies allow for individualized information specific to the extracellular and total-body fluid with increased accuracy and without the need for normalized population-specific algorithms. [8,9] On August 18th, the patient's diastolic PA pressure decreased to 11 mmHg from a previous measure of 13 mmHg (August 16th). Because of his fatigue coupled with objective data, it was decided he was dehydrated.…”
Section: Introductionmentioning
confidence: 88%
“…These end-spectrum frequencies allow for individualized information specific to the extracellular and total-body fluid with increased accuracy and without the need for normalized population-specific algorithms. [8,9] On August 18th, the patient's diastolic PA pressure decreased to 11 mmHg from a previous measure of 13 mmHg (August 16th). Because of his fatigue coupled with objective data, it was decided he was dehydrated.…”
Section: Introductionmentioning
confidence: 88%
“…Bioimpedance spectroscopy has emerged as a potential method to detect subtle changes in thoracic fluid content HF patients [24,25]. A feasibility study using the BIM sensor for home TM has been conducted, where it was shown to predict episodes of hospitalization for worsening HF [SCHAUERTE P, UNPUBLISHED DATA].…”
Section: Spectroscopic Bioimpedancementioning
confidence: 99%
“…Although the additional body signals relevant in assessing and improving overall human body (workers') health conditions today might be used trough: artificial cochlea, artificial retina, camera pill, carbon dioxide sensor, visual sensor, bio-impedance spectroscopy, chipped sweatbands, etc. [17][18][19][20], for the purpose of this study, the attention will be put to the firstly listed ones.…”
Section: Safety and Health Management In The Port Of Barmentioning
confidence: 99%